Analysis of Adolescents' Ability to use Standard Language in Daily Activities - Junaida Junaida (Indonesian Journal Education, 2025)
The diversity of language use in the surrounding environment reflects the richness of the Indonesian nation in terms of language and culture. The diversity of languages spread across various regions demonstrates that language is a vital part of a nation's identity. This research uses a literature review method, an approach that focuses on collecting, analyzing, and summarizing the results of previous research and expert opinions on the topic under study. The results show that language plays a crucial role in national identity and as a form of respect for the country. The younger generation should be able to maintain and uphold the Indonesian language as a manifestation of love and devotion to the homeland. However, in reality, the use of non-standard language is increasingly common in everyday life and is even considered commonplace. The influence of foreign languages and the flow of modernization are among the factors causing the emergence of slang among teenagers. This phenomenon is slowly shifting the position of standard Indonesian, whose sustainability should be maintained.